Transition-Metal-Free Synthesis of Thiosulfonates through Radical Coupling Reaction - Zhou, Guodong; Xu, Xu-Dong; Chen, Gan-Ping; Wei, Wen-Ting; Guo, Zhiyong (Synlett, 2018)
An efficient and practical transition-metal-free radical coupling reaction of sulfonyl hydrazides mediated by NIS/K2S2O8 has been developed to afford a variety of biological activity thiosulfonates in moderate to excellent yields. Compared to a known approach for the synthesis of thiosulfonates from sulfonyl hydrazides, this strategy features high yields, mild reaction conditions, and broad substrate scope. The mechanistic studies revealed that the procedure undergoes via a radical cross-coupling process for the construction of S–S bonds.
Keywords: transition-metal-free; radical coupling reaction; S–S bonds; thiosulfonates